Work-Related Flow: The Development of a Theoretical Framework Based on the High Involvement HRM Practices With Mediating Role of Affective Commitment and Moderating Effect of Emotional Intelligence - Wang, Xiaochen; Shaheryar, (Frontiers in Psychology, 2020)
The long-term success of organizations is mainly attributable to employees’ psychological health. Organizations focusing on promoting and managing the flow (an optimal experience and optimal functioning state) may enhance employees’ well-being and performance to an optimum level. Surprisingly, the literature representing the role of HRM practices for their effect on work-related flow (i.e., intrinsic motivation, absorption, and work enjoyment) is very sparse. Accordingly, by drawing primarily on the job demands-resources model and HRM specific attribution theory, this paper develops a theoretical framework that unravels the effectiveness of specific organizational level High Involvement HRM (HIHRM) practices (i.e., recognition, empowerment, information sharing, fair rewards, and competence development) in activating the individual level work-related flow with beneficial effect and mediating role of affective commitment. In addition to highlighting the underlying mechanisms that may cause HIHRM practices to be regarded as resources and sometimes as demands, this paper especially proposes that these practices implemented with a focus to promote employee well-being are perceived as job resources and may positively influence affective commitment and flow, whereas these practices used as a demand to increase performance are perceived as job demands and may hinder affective commitment and flow. It is further significant to understand the possible moderating effects of emotional intelligence on the relationships among HIHRM practices, affective commitment, and flow. The paper augments the knowledge and understanding of the impact process of HIHRM practices, in particular how the HIHRM effect is sensed by the workers and thus, influences their succeeding job attitude and work experience. Finally, this work, as the first paper to link HIHRM practices with work-related flow, promotes the concept of positive psychology in the workplace.